‘FESTIVAL’ SEBLANG OLEHSARI BANYUWANGI 2018-2022 - Vindriana, Nuri Dwi; Simatupang, Gabriel Roosmargo Lono Lastoro; Christian Richardus, Wisma Nugraha (Universitas Gadjah Mada, 2023)
The Seblang Olehsari ‘Festival’ is a cultural celebration that comes from a ritual. The ritual is held by the people of Olehsari village as an 'action' of fulfilling an ancestral will. Its main function is as a village clean ceremony and a medium of friendship between the real world (microcosm) e and the supranatural world (macrocosm) which has been going on for decades. As a performance, Seblang Olehsari has the characteristics of using dance as the media which is demonstrated by the Seblang dancers in a trance or kejiman. The existence of Seblang Olehsari is currently growing side by side with the growth of the creative industry, so that in the process of its implementation, it has image branding or the empowerment strategy for cultural event destinations. This study aims to present a festival discourse that departs from rituals along with traditional values. The perspective of event studies is used to classify event typologies and analyze the festivalization phenomenon towards Seblang Olehsari ritual. The use of the festival platform caused a main event shift from a religious event (ritual) to a festival event. It has also an impact on socio-cultural changes or the public's point of view in viewing culture, especially on nowadays rituals. Keywords: Banyuwangi, Event Studies, Festival, Ritual, Seblang Olehsari